The Ghosts of Justice and the Law of Historical Memory - Mónica López Lerma (Conserveries Mémorielles)
Drawing on the ethico-political relationship between memory and justice in the sense proposed by Walter Benjamin and Jacques Derrida, this article addresses the recovery of the historical memory of the victims of Francisco Franco’s dictatorship (1939–1975). It does so by contrasting Antonio Muñoz Molina’s novel Beltenebros (Prince of Shadows, 1989) and the recent Spanish “Law of Historical Memory” (2007). In juxtaposing the novel and the current law, it aims to trace in each text a series of recurring representational practices (words, images, expressions) that seek to do justice to the victims, with unequal success. The novel’s recurring expressions (i.e., shadows, the repressed, eternal return, ghosts, and blindness) stress the importance of coming to terms with the “ghosts of the past.” The law focuses instead on other words and images (i.e., foundation, reconciliation, concord, and closure) that allude to the idea of historical progress, it will be argued, without proper acknowledgment of the injustices of the past. In doing so, the law becomes a commemorative site for the Spanish Transition, but not for the recovery of the victims’ memory. The law’s re-appropriation of the “spirit of the Transition” reveals Spain’s deep fear of confronting the ghosts of the past, a fear that can be perceived still today.